Observation of ionomer in catalyst ink of polymer electrolyte fuel cell using cryogenic transmission electron microscopy. (10th January 2017) - Takahashi, Shinichi; Shimanuki, Junichi; Mashio, Tetsuya; Ohma, Atsushi; Tohma, Hajime; Ishihara, Ayumi; Ito, Yoshiko; Nishino, Yuri; Miyazawa, Atsuo
Abstract: Optimizing the catalyst layer structure is one of the key issues for improving performance despite lower platinum loading. The catalyst ink, consisting of platinum-loaded carbon particles and ionomer dispersed in an aqueous solvent, is a key factor for controlling the structure of the catalyst layer because the catalyst layer is prepared in a wet coating process. For that purpose, we visualized the nanostructure of the ionomer in the catalyst ink by cryogenic electron microscopy, especially cryogenic transmission electron microscopy (cryo-TEM). By cryo-TEM, it was revealed that ionomer molecules formed rod-like aggregates macro-homogeneously in the solvent, and a similar morphology was observed in a carbon-particle-containing solvent. In contrast, ionomer aggregates in the catalyst ink containing platinum nanoparticles loaded on carbon particles were denser in the vicinity of the platinum-loaded carbon particles. That can be attributed to strong interaction between platinum nanoparticles and sulfonic acid groups in the ionomer. It also implies that a good understanding of ionomer morphology in the catalyst ink can play an important role in controlling the catalyst layer microstructure for reducing platinum loading.